From Music to Big-Music: Listening in the age of Big Data - Koutsomichalis, Marinos (My University, 2016)
Following a series of technological breakthroughs and the proliferation of new, cloud-based media, listening in the 21st century has become dynamic, fragmented, interactive and distributed. Contemporary audiences are typically expected to traverse (big) music databases and, employing several overlapping interfaces, to resynthesize, rather than to merely access, content. On this construal, new ways of both experiencing and thinking about music have been laid out. This article attempts to sketch the “big music” phenomenon, discussing its genesis, outlining its implications and, finally, suggesting a typology for the classification of its carrier media.